Factors Associated with the Initiation of Added Sugar among Low-Income Young Children Participating in the Special Supplemental Nutrition Program for Women, Infants, and Children in the US - Morium B. Bably (MDPI AG, 2021)
Added sugar intake at a young age is associated with chronic diseases including cardiovascular diseases, asthma, elevated blood pressure, and overweight. The Dietary Guidelines for Americans 2020–2025 and the American Heart Association recommend delaying the introduction of added sugar until age 2. The aims of this study were to identify the timing of added sugar initiation; factors associated with added sugar initiation; and the top five added sugar foods and beverages consumed by infants and children at three age ranges (<7 months, 8–13 months, and 14–24 months). Data were from the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) Infant and Toddler Feeding Practices Study-2, a longitudinal, national population of WIC participants enrolled in WIC eligible clinics (n = 3835). The Cox proportional hazards model was used to examine the factors associated with introducing added sugar. About 25% of children were given added sugar at or before 7 months. Contributing factors were caregivers’ race/ethnicity, education, employment, weight status, parity, child sex, and premature birth (all p < 0.05). The top added sugar foods consumed between 1–24 months were cereal, crackers, apple sauce, dessert, yogurt, sweetened beverages, syrup and preserves, and cookies. Further research to examine the impact of early initiation of added sugar on health outcomes and taste preferences is warranted.